Compliance to warfarin among cardiovascular disease patients, King Narai Hospital, Lopburi province - ่่Janampon Janchudagorn; Boonshuyar, Chaweewon; Ivanovitch, Katiya (Journal of Medical and Public Health Region 4, 2023)
This descriptive study aimed at assessing compliance to warfarin and finding the relationship between knowledge, attitude, social support with compliance to warfarin among cardiovascular disease patients in King Narai Hospital, Lopburi province. Data were collected from March to June 2022 by in-person interviews and warfarin registry network program (WaRN) of 250 patients. Descriptive statistics and binary logistic regression at 5% significance level were adopted for the analysis. Results showed that 61.2% omplied with warfarin, 74.0%, 26.4% and 88.8% had good level of knowledge, attitude, and perception of social support respectively, 10.8% was current alcohol drinker. Non-alcohol drinkers complied to warfarin more than the drinkers (AOR=3.73, 95%CI:1.35-10.28). The shorter the duration of warfarin intake (2-5 years) was the better the compliance (AOR=3.01, 95%CI:1.53-5.95). The good level of knowledge complied to warfarin more than those at poor level (AOR=4.09, 95%CI:1.24-13.51). Those at good of attitude complied to warfarin more than those at the lower level (AOR=3.16, 95%CI:1.49-6.69). However, the relationship between social support and the compliance was not significant (AOR=1.54, 95%CI:0.56-4.19). To improve the warfarin compliance, provision of knowledge, attitude on taking warfarin is suggested every time the patients come to warfarin clinic as well as a joint plan with caregivers and close relatives to reduce and stop unhealthy health behaviors.